Effect of aeration on steady-state conditions in non- and partially aerated low-loaded biofilter - Albuquerque, Antonio (2014)
Excessive growth of biomass and retention of solids associated with air bubbles lead to bed clogging, which affects the biofilters' performance. Two experiments were carried out in a submerged biofilter at the flow velocity of 0.5 m h(-1), for an organic loading rate of 51 g C m(-3) h(-1) and a nitrogen loading rate of 13 g NH4-N m(-3) h(-1), one with the biofilter not aerated, the other with the biofilter partially aerated. The results showed that the higher head losses occurred in the upper section of the biofilter, where there was a greater biomass development and a higher removal of organic carbon, ammonia and solids, with the maximum allowed head loss being reached in 16 and 8 days. In any case, the steady-state conditions were achieved after 2 days and were interrupted on the tenth day of experiment E1 and on the fifth day of experiment E2. This allowed defining different operating cycles that enabled an average organic removal rate of 12.7 g C m(-3) h(-1) (27 %) and an average ammonia removal rate of 1.1 g NH4-N m(-3) h(-1) (9 %) without aeration, and of 35.8 g C m(-3) h(-1) (76 %) and 6.3 g NH4-N m(-3) h(-1) (51 %) with aeration. Regardless of the aeration conditions, more than 90 % of TOC and NH4-N removal occurred in the upper section. After the backwashing cycle, the biofilter returned to steady-state conditions in 6 h (without aeration) and 7 h (with aeration).